Structure of the Wechsler Intelligence Scale for Children – Fourth Edition in a Group of Children with ADHD - Gomez, Rapson; Vance, Alasdair; Watson, Shaun D. (Frontiers in Psychology, 2016)
Objective: This study used confirmatory factor analysis to examine the factor structure for the 10 core WISC–IV subtests in a group of children (N = 812) with ADHD. Method: The study examined oblique four- and five-factor models, higher order models with one general secondary factor and four and five primary factors, and a bifactor model with a general factor and four specific factors. Results: The findings supported all models tested, with the bifactor model being the optimum model. For this model, only the general factor had high explained common variance and omega hierarchical value, and it predicted reading and arithmetic abilities. Conclusion: The findings favor the use of the FSIQ scores of the WISC-IV, but not the subscale index scores.